Insect Diversity and Ecological Functions in the Isyo Hills Rhepang Muaif Nimbokrang Forest Park, Jayapura Regency - Euniche R.P.F. Ramandey; Evie L. Warikar (Jurusan Biologi FMIPA Universitas Cenderawasih, 2025)
Insects have a very important role in maintaining the balance of the forest ecosystem and supporting the continuity of life in the forest. The main roles of insects in the forest include as pollinators, predators, decomposers, pest controllers and as indicators of environmental health. However, there is no data regarding the diversity and ecological function of insects in the Isyo Hills Rhepang Muaif tourist forest. Insect sampling technique uses the scan sampling method. Insect diversity data is analyzed using the Shannon-Wiener species diversity index. Based on research conducted in the Isyo Hills Rhepang Muaif Tourism Forest, Nimbokrang District, Jayapura Regency, a total of 606 individual insects were found with 54 types of insects representing 8 different orders, namely: Order Lepidoptera (26 types= 48%), Orthoptera (7 types= 13%), Coleoptera (6 types= 11%), Hemiptera (6 types= 11%), Odonata (4 types= 7%), Hymenoptera (2 types = 4%), Diptera (2 types = 4%) and the Order Blattodea (1 type= 2%). The results of the analysis show that species diversity in each insect order is in the medium and low categories. The Shannon-Wiener index (H') value for each order ranges from 0–2.99. Insects obtained from sampling results fall into eight levels of important ecological roles (feeding groups/ functional groups/trophic guilds) in nature, namely pollinators, phytophagous, xylophagous, predators, omnivores, carnivores, granivores and detrivores